2019
DOI: 10.1111/vco.12548
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective comparison of first‐line adjuvant anthracycline vs metronomic‐based chemotherapy protocols in the treatment of stage I and II canine splenic haemangiosarcoma

Abstract: Splenectomy followed by adjuvant chemotherapy is commonly used to treat canine splenic haemangiosarcoma (HSA), although it is unclear if different treatment protocols may have a similar efficacy. The objective of this retrospective study was to assess outcome in dogs with stage I and II splenic HSA treated with either first‐line adjuvant anthracycline (AC) or metronomic (MC)‐based chemotherapy protocols, by comparing median time to progression (TTP) and median survival time (MST). Medical records of nine insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 24 publications
4
46
0
1
Order By: Relevance
“…Complete excision was performed in four of the five dogs despite adhesions to adjacent anatomic structures, specifically the ureters and urinary bladder. Although post‐chemotherapy survival data was only available for one dog in the current case series, survival time in this dog is consistent with recent studies evaluating adjunct chemotherapy following surgery for HSA 27–30 . Marconato et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Complete excision was performed in four of the five dogs despite adhesions to adjacent anatomic structures, specifically the ureters and urinary bladder. Although post‐chemotherapy survival data was only available for one dog in the current case series, survival time in this dog is consistent with recent studies evaluating adjunct chemotherapy following surgery for HSA 27–30 . Marconato et al.…”
Section: Discussionsupporting
confidence: 88%
“…Treggiari et al. reported overall MST for stage I and II splenic HSA to be 338 days and 151 days, with surgical intervention and anthracycline chemotherapy yielding an MST of 154 days, surgical intervention and metronomic chemotherapy yielding an MST of 225 days, and surgical intervention and anthracycline with metronomic chemotherapy yielding an MST of 338 days 29 . Alexander et al.…”
Section: Discussionmentioning
confidence: 99%
“…This was surprising considering differences have been shown with DOX-based studies between dogs with the different stages of splenic HSA. [33][34][35] Our interest in determining if peripheral blood monocyte counts could predict survival stemmed from 2 different studies. A study showed that an increased infiltration of CD18 + macrophages was found preferentially in HSA compared with other tumor-types.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to treatment for sarcomas, a general review highlights emerging therapeutic approaches for canine sarcomas, while the potential of combined targeted Type I interferon pathway inhibitors and oncolytic viruses to treat sarcomas are discussed in a second review . Original research publications within this issue also report treatment outcomes for canine patients treated with metronomic or anthracycline‐based adjuvant chemotherapy protocols, stereotactic radiation therapy for multilobular osteochondrosarcoma, limb sparing in dogs using three‐dimensional printed endoprosthesis and outcome of dogs undergoing secondary amputation for complications related to limb salvage surgery for osteosarcoma . This special issue also includes two original research manuscripts that aim to better understand potential contributions of the immune landscape in the biology or outcome of injection site sarcoma and canine osteosarcoma …”
mentioning
confidence: 99%